KONSELING DIGITAL DAN DUKUNGAN AI DALAM PENGEMBANGAN SUMBER DAYA MANUSIA: TINJAUAN SISTEMATIS - Sigit Hariyadi; Widya Novi Angga Dewi; Binti Isrofin; Ernest Ceti Septyanti; Awalya; Joko Sutarto (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The Indonesian employee mental health crisis issue can be mitigated through the innovation of digital counseling and the support of artificial intelligence (AI). This research adopts the approach of a systematic literature review (SLR) with the aid of the PRISMA technique covering twelve (12) articles published between 2021 and 2025 from the databases of Science Direct, PubMed, SAGE Open, and Taylor and Francis. The research aimed to determine the efficacy of digital counseling and AI on employees' psychological well-being, productivity, and retention, and to identify the facilitators and barriers to implementation. Additionally, it sought to ascertain the ethical issues arising from the recommendations of governance theories. The research showed that digital counseling can improve accessibility and reduce stigma; however, it is ineffective in addressing issues related to data privacy and unresolved emotions associated with AI. The positive impact on adoption is determined by corporate social responsibility, emotional support from leaders, and organizational supportive features. To summarize, the meaningful integration of humans and digital counseling, coupled with thorough ethical governance structures and genuine leadership, is crucial to the success of digital counseling and organizational performance.